Deletion of LRP1 From Astrocytes Modifies Neuronal Network Activity in an in vitro Model of the Tripartite Synapse - Romeo, Ramona; Glotzbach, Kristin; Scheller, Anja; Faissner, Andreas (Frontiers in Cellular Neuroscience, 2021)
The low-density lipoprotein receptor-related protein 1 (LRP1) is a transmembrane receptor that binds over 40 potential ligands and is involved in processes such as cell differentiation, proliferation and survival. LRP1 is ubiquitously expressed in the organism and enriched amongst others in in blood vessels, liver and the central nervous system (CNS). There, it is strongly expressed by neurons, microglia, immature oligodendrocytes and astrocytes. The constitutive LRP1 knockout leads to embryonic lethality. Therefore, previous studies focused on conditional LRP1 knockout strategies and revealed that the deletion of LRP1 causes an increased differentiation of neural stem and precursor cells into astrocytes. Furthermore, astrocytic LRP1 is necessary for the degradation of Aβ and the reduced accumulation of amyloid plaques in Alzheimer’s Disease. Although the role of LRP1 in neurons has intensely been investigated, the function of LRP1 with regard to the differentiation and maturation of astrocytes and their functionality is still unknown. To address this question, we generated a triple transgenic mouse model, where LRP1 is specifically deleted from GLAST-positive astrocyte precursor cells. The recombination with resulting knockout events was visualized by the simultaneous expression of the fluorescent reporter tdTomato. We observed a significantly increased number of GLT-1 expressing astrocytes in LRP1-depleted astrocytic cultures in comparison to control astrocytes. Furthermore, we investigated the influence of astrocytic LRP1 on neuronal activity and synaptogenesis using the co-culture of hippocampal neurons with control or LRP1-depleted astrocytes. These analyzes revealed that the LRP1-deficient astrocytes caused a decreased number of single action potentials as well as a negatively influenced neuronal network activity. Moreover, the proportion of pre- and postsynaptic structures was significantly altered in neurons co-cultured with LPR1-depleted astrocytes. However, the number of structural synapses was not affected. Additionally, the supernatant of hippocampal neurons co-cultured with LRP1-deficient astrocytes showed an altered set of cytokines in comparison to the control condition, which potentially contributed to the altered neuronal transmission and synaptogenesis. Our results reveal astrocytic LRP1 as a modulator of synaptic transmission and synaptogenesis by altering the expression of glutamate transporter on the cell surface on astrocytes and the release of cytokines in vitro.